THREE NEW BOMOLOCHIDS PARASITIC ON FISHES OF THE KERALA COAST - Pillai, N Krishna (Indian Journal of Fisheries, 2011)
Three bomoloohids, Holobomolochus nemipteri sp. nov, Nothohomolochus quadriceros sp. nov, and N. genesi sp. nov parasitic on tlie flslies of the Kerala coast are described